2002
DOI: 10.1007/s00737-002-0001-5
|View full text |Cite
|
Sign up to set email alerts
|

A clinical trial of adjunctive oestrogen treatment in women with schizophrenia

Abstract: A double-blind, 28-day, placebo-controlled study was conducted with three groups of women of child-bearing age (N = 12 in each group) who received standardised antipsychotic medication plus a) 50 microg transdermal estradiol or b) 100 microg transdermal estradiol or c) transdermal placebo. Preliminary analyses show that women receiving 100 microg of estradiol made greater improvements in the symptoms of schizophrenia than either the 50 microg estradiol or placebo groups. The addition of 100 microg adjunctive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 14 publications
2
33
0
1
Order By: Relevance
“…A few studies have suggested a relationship between estrogen and negative symptoms in schizophrenia. Kulkarni et al [19,31] showed that estradiol adjuvant treatment with antipsychotics has a beneficial effect on positive symptoms, and partially on negative symptoms in women with the acute phase of schizophrenia. Interestingly, in a study on postmenopausal schizophrenia, Lindamer et al [18] showed that HRT users received lower average daily doses of antipsychotic medication, and that they had less severe negative symptoms compared with women who did not use HRT.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have suggested a relationship between estrogen and negative symptoms in schizophrenia. Kulkarni et al [19,31] showed that estradiol adjuvant treatment with antipsychotics has a beneficial effect on positive symptoms, and partially on negative symptoms in women with the acute phase of schizophrenia. Interestingly, in a study on postmenopausal schizophrenia, Lindamer et al [18] showed that HRT users received lower average daily doses of antipsychotic medication, and that they had less severe negative symptoms compared with women who did not use HRT.…”
Section: Discussionmentioning
confidence: 99%
“…Males typically have an earlier age of onset and more severe symptoms and tend to be less treatment responsive than females with schizophrenia (3). However, women with schizophrenia can have symptom exacerbation at times of low estrogen: during post-partum and menopause (4 -6), and schizophrenic symptoms can be ameliorated with estrogen treatment (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…The authors recommended future trials as their n of 214 was too small for clinical application. The majority of the studies were done by Kulkari, in 2001 [21], 2002 [22] and 2008 [23]. These were all done using unopposed estrogen as an adjunct to neuroleptics over a 28 day period to treat acute psychosis in women with an average age of 32-34(much younger than our cases).…”
Section: Etiology Of Schizophrenia Presenting During Menopausal Transmentioning
confidence: 97%
“…Usual treatments are oral estradiol 1 mg daily or equine estrogen 0.625 mg daily or weekly patch with estradiol 0.05 mg/daily. Additionally, these formulations of estrogen were found to be effective in the studies of women with schizophrenia [21][22][23].…”
Section: Ert: Women Without a Uterusmentioning
confidence: 99%